The Arabidopsis NOT4A E3 ligase promotes PGR3 expression and regulates chloroplast translation - Mark Bailey; Aiste Ivanauskaite; Julia Grimmer; Oluwatunmise Akintewe; Adrienne C. Payne; Rory Osborne; Anne-Marie Labandera; Ross D. Etherington; Marjaana Rantala; Sacha Baginsky; Paula Mulo; Daniel J. Gibbs (Nature Communications, 2021)
NOT4 proteins associate with ribosomes and are required for co-translational quality control in yeast and animals. Here, Bailey et al. show that Arabidopsis NOT4A positively regulates the expression of the nuclear encoded pentatricopeptide repeat (PPR) protein PGR3 and is required for ribosome biogenesis and mRNA translation in the chloroplast.